2014
DOI: 10.1111/jonm.12204
|View full text |Cite
|
Sign up to set email alerts
|

A reflective framework to foster emotionally intelligent leadership in nursing

Abstract: The proposed framework may supplement learning about emotional intelligence skills and aid the integration of emotional intelligence in a clinical environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 43 publications
1
25
0
2
Order By: Relevance
“…The students have shown that there is a type of care that is not always experienced as good for the patients. Identifying and acknowledging the experience of need, both from oneself and from others, and being able to provide support for those who need it becomes crucial (Heckemann et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The students have shown that there is a type of care that is not always experienced as good for the patients. Identifying and acknowledging the experience of need, both from oneself and from others, and being able to provide support for those who need it becomes crucial (Heckemann et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This may create a climate of distrust between staff and leaders (Udod & Care 2013). Therefore, due to the ever-changing work scenarios leading with emotional intelligence may be regarded as a means to bridge this gap (Heckemann, Schols & Halfens, 2015). Leaders equipped with emotional intelligence may anticipate that group member's behavior and encourage them to share norms, behaviors, basic assumptions that would improve their team's effectiveness.…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 99%
“…Leaders with emotional intelligence are high performers who contribute to organizational success. Emotional intelligence increases in leaders by having them explore, analyze, and foster their EI leadership skills (Heckemann, Schols, & Halfens, 2015).…”
Section: Emotional Intelligencementioning
confidence: 99%
“…Senior nurse leaders need to show new nurse managers how to manage their emotions to create positive work environments (Heckemann et al, 2015).…”
Section: Emotional Intelligencementioning
confidence: 99%